PREVALENCE OF MALNUTRITION AMONG SCHOOL CHILDREN WITH REFERENCE TO OVERWEIGHT AND OBESITY AND ITS ASSOCIATED FACTORS - Rawat, Ranu; Garg, S K; Chopra, H; Bajpai, S K; Bano, Tanveer; Jain, S; Kumar, A (Indian Journal of Community Health, 2012)
Research Question: What influence does diet and physical activity have on the occurence of overweight and obesity in school aged children? Objectives: To study the diet and physical activity factors influencing overweight and obesity in school aged children. Study Design: Cross sectional Study. Settings: Field Practice area of Department of Community Medicine, LLRM Medical College, Meerut. Participants: 400 children between 5-14 years age group Statistical Analysis: Chi Square Test Results: The prevalence of overweight and obesity in children was 9.8% and 3.7% respectively. Among dietary factors, a significant association was seen in the prevalence of overweight and obesity with consumption of >3 meals per day(P<0.001), habit of eating in between meals(P<0.05) and in having dinner as the heaviest meal of the day (P<0.02). Among physical activity factors, a significant association was seen in the prevalence of overweight and obesity with the habit of not playing outdoor games (P<0.001), not participating in household activities(P<0.001), using some vehicular transport to go to school (P<0.001) and watching T.V. for more than 3hrs/day(P<0.001).Conclusion:Diet and Physical activity have an influence on occurrence of overweight and obesity in school aged children. Dietary and lifestyle modification must be advised to children to prevent occurrence of overweight and obesity in them.